Biogas flame propagation in the interconnected pipe: The effect of biogas/air mixture concentration - N. S., Noor Azmi; Siti Zubaidah, Sulaiman; A., Ramli; R. M., Kasmani; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Nur Aqidah, Muhammad Harinder Khan; N. H., Semawi (IOP Publishing, 2019)
Flame propagation in the interconnected pipe with various size has a potential to initiate an explosion hazard. Thus in this study, the biogas/air flame propagation was investigated in the interconnected pipe. The experiment was conducted in pipe interconnected with three different diameters which are 5 cm, 10 cm and 46 cm respectively. The biogas is mixed with the ratio of 60:40 of methane and carbon dioxide. The concentration of biogas/air was varied at ER: 0.8 - 1.4 respectively. The mixtures were ignited using a spark plug. The pressure and flame speed were measured using thermocouples K type and pressure transducers located along the rig. Pure methane was also tested to examine the effect of CO2 on the biogas flame propagation. From the experimental analysis, the highest maximum overpressure (2.5 bar) and flame speed (41.9 m/s) were recorded at the smallest pipe diameter (0.5 cm) at rich concentration, ER = 1.2 and 1.4 respectively. The results show that the thermal diffusive effect is one of the factors contributed to the flame propagation that resulted to the increase of the maximum overpressure and flame speed. However, the presence of CO2 in biogas makes the biogas explosion is less severe as compared to the methane.